Assessment of dietary fish consumption in pregnancy: comparing one-, four- and thirty-six-item questionnaires. Issue 9 (24th July 2013) - Oken, Emily; Guthrie, Lauren B; Bloomingdale, Arienne; Gillman, Matthew W; Olsen, Sjurdur F; Amarasiriwardena, Chitra J; Platek, Deborah N; Bellinger, David C; Wright, Robert O
Abstract Objective Fish consumption influences a number of health outcomes. Few studies have directly compared dietary assessment methods to determine the best approach to estimating intakes of fish and its component nutrients, including DHA, and toxicants, including methylmercury. Our objective was to compare three methods of assessing fish intake. Design We assessed 30 d fish intake using three approaches: (i) a single question on total fish consumption; (ii) a brief comprehensive FFQ that included four questions about fish; and (iii) a focused FFQ with thirty-six questions about different finfish and shellfish. Setting Obstetrics practices in Boston, MA, USA. Subjects Fifty-nine pregnant women who consumed ≤2 monthly fish servings. Results Estimated intakes of fish, DHA and Hg were lowest with the one-question screener and highest with the thirty-six-item fish questionnaire. Estimated intake of DHA with the thirty-six-item questionnaire was 4·4-fold higher (97 v. 22 mg/d), and intake of Hg was 3·8-fold higher (1·6 v. 0·42 μg/d), compared with the one-question screener. Plasma DHA concentration was correlated with fish intake assessed with the one-question screener (Spearman r = 0·27, P = 0·04), but not with the four-item FFQ (r = 0·08, P = 0·54) or the thirty-six-item fish questionnaire (r = 0·01, P = 0·93). In contrast, blood and hair Hg concentrations were similarly correlated with fish and Hg intakes regardless of the assessment method (r = 0·35 to 0·52). Conclusions A longer questionnaire provides no advantage over shorter questionnaires in ranking intakes of fish, DHA and Hg compared with biomarkers, but estimates of absolute intakes can vary by as much as fourfold across methods.